Morphological and molecular characterization of Colletotrichum species from herbaceous plants in Thailand - Photita W. (2014)
Thirty-four isolates of Colletotrichum spp. were isolated from banana, ginger, Euphatorium thymifolia, soybean, longan, mango and Draceana sanderiana. They included endophytes from healthy plants and probable pathogens from disease lesions. Isolates were identified and grouped based on colony morphology, and size and shape of appressoria and conidia. Molecular analysis based on sequences of the rDNA internal transcribed spacers (ITS1 and ITS2), indicated that the Colletotrichum isolates comprised four clades that paralleled the morphological groupings. Most isolates clustered within three distinct clades which potentially represented different species. Endophytes isolated from different hosts are more likely to be the same species. Colletotrichum musae was positioned close to the C. gloeosporioides clades. Morphological and phylogenetic analysis of Colletotrichum pathogens and endophytes showed that endophytic isolates were most similar to C. gloeosporioides however, no pathogenic isolates clustered with endophytic isolates. The correlation between morphological and molecular-based clustering demonstrated the genetic relationships among the isolates and species of Colletotrichum and indicated that ITS rDNA sequence data were potentially useful in taxonomic species determination.